Сontact pressure determiantion in radial two-row bearings with barrel-like rollers - Чернишенко, Александр Вячеславович; Фесенко, Геннадий Иванович; Мельниченко, Александр Анатольевич (Eastern-European Journal of Enterprise Technologies, 2012)
The questions related to the calculation of contact stress in two-row radial bearings with a barrel-shaped rollers. Obtained in the study method gives more accurate results, by definition, time-mers of the contact between the rings and rolling elements in bearings